#TITLE_ALTERNATIVE# - PEBRIANTI (NIM 10504069), TINA
Carbon paste electrode has been commonly used in voltametric measurement for determination of trace metal. Mercury electrodes were usually used as working electrode in stripping voltammetry owing to their high sensitivity, reproducibility, and renewability. However, because of the toxicity of mercury, alternative electrodes are highly needed. In this research, silica based carbon paste electrode has been plated with thin bismuth layer for the measurement of Pb2+ and Cd2+ solution using square wave anodic stripping voltammetry technique. For both in-situ and ex-situ measurements of Pb2+ ion, optimum composition of the modified carbon-paste electrode contained 25% of silica. Optimum pH of Pb2+ ion measurement using both methods was 4,5. Optimum ratio of Bi to analite concentration was 10:1 for in situ measurement. Repeated measurement of Pb2+ ion showed that ex situ method provide better precision than in situ method because of ex-situ measurement has lower standard deviation, which is 2.58%. From ex-situ measurement it was found that calibration curve is linear in the range of 10-1000 ppb with detection limit of 6.46 ppb for Pb2+ and 6.41 ppb for Cd2+. Accuracy of the measurement was quite good with percent recovery between 97 %-106%.